Electronic Communication across Porphyrin Hexabenzocoronene Isomers. Issue 26 (20th May 2019) - Martin, Max M.; Lungerich, Dominik; Haines, Philipp; Hampel, Frank; Jux, Norbert
Abstract: Single‐molecule electronic components (SMECs) are envisioned as next‐generation building blocks in quantum circuit systems. However, challenges such as the reproducibility of the electrode attachment to the individual molecules hamper their fundamental investigation. For our purpose, we introduced quasi optoelectronic electrodes (QOEs) that allow for rapid investigations of the properties and suitability of compounds for molecular electronic devices. In particular, we probed hexa‐peri‐hexabenzocoronene (HBC) as a model system for D 6 h ‐symmetrical nanographenes, with porphyrins as QOEs attached to the periphery. We prepared selectively bis‐porphyrin‐functionalized HBCs with ortho ‐, meta ‐ and para ‐substitution and studied their communication properties, in correlation to the geometrical alignment and size of the system, by electrochemistry and optical spectroscopy. Further insights into structure–property relationships were gained by DFT calculations and X‐ray diffraction analysis. Abstract : Clear communication : Hexabenzocoronene was utilized as a model system for nanographenes and probed spectroscopically through peripherally attached porphyrins that served as quasi optical electrodes. Nanographenes functionalized selectively in the ortho ‐, meta ‐, and para ‐positions showed differences in the electronic communication between the porphyrins, which is reflected by a distortion of the B‐band.